IDENTIFICATION OF SCIENCE-PHYSICS CONCEPTS IN THE TRADITIONAL GAME OF BAMBU GILA AND ITS IMPLEMENTATION IN LEARNING - Anatasija Limba; Elsina S Tamaela; Fryan Sopacua; Ledy Manuhutu; Imanuel V Huwae (EDU SCIENCES JOURNAL, 2023)
Local wisdom is ideas, thoughts, values, and views that are wise, valuable, inherent, and adhered to by the local community. It is typical of an area regarding cultural, economic, communication, and ecological aspects, as well as the attitudes that are created naturally and come from customs or ancestral teachings. Implementation of local wisdom in learning is important for teachers today, such as traditional games. The implementation of traditional games in learning is expected to reduce the widespread use of gadgets and their negative impacts such as forming an individualistic and opportunistic habit pattern in children. One of the popular traditional games in Maluku is bambu gila. This study aims to identify science-physics concepts in the traditional game of bambu gila, map the concepts identified at each junior and senior high school level and identify how to implement them in learning. The research was conducted using a descriptive method with a qualitative approach. Data were collected through observation and interviews related to the traditional game of bambu gila with bambu gila handlers and documents study related to physics concepts. The results showed that the science-physics concepts identified in the bambu gila included the concepts of displacement, force, work, and energy. These concepts can be taught at junior and senior high school levels using the Kurikulum 2013 and the independent curriculum. These concepts can be taught by defining the concepts to be taught, clarifying concepts according to the steps of bambu gila, and developing learning tools (lesson plan, worksheet, teaching materials, and assessments) that are combined with the traditional game of bambu gila.